2021
DOI: 10.1101/2021.03.05.434072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut markers of bodily self-consciousness

Abstract: Bodily self-consciousness, the state of mind that allows humans to be aware of their own body, forms the backdrop for almost every human experience, yet its underpinnings remain elusive. Here we use an ingestible, minimally invasive capsule and surface electrogastrography to probe if gut physiology correlates with bodily self-consciousness during a virtual bodily illusion. We discover that specific patterns of stomach and large intestine activity (temperature, pressure, pH, and gastric peak frequency) covary w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Regarding the association between gastric-alpha PAC and negative body image, emerging evidence indicates that the stomach and the brain influence each other via bidirectional (i.e., both ascending and descending) pathways (Mayeli et al, 2021;Monti et al, 2021;Rebollo et al, 2018;Richter et al, 2017). Specifically, in the initial identification of gastric-alpha PAC, transfer entropy analysis indicated that gastric-alpha coupling is attributable to an ascending influence from the stomach to the brain (Richter et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the association between gastric-alpha PAC and negative body image, emerging evidence indicates that the stomach and the brain influence each other via bidirectional (i.e., both ascending and descending) pathways (Mayeli et al, 2021;Monti et al, 2021;Rebollo et al, 2018;Richter et al, 2017). Specifically, in the initial identification of gastric-alpha PAC, transfer entropy analysis indicated that gastric-alpha coupling is attributable to an ascending influence from the stomach to the brain (Richter et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogel capsules are a minimally invasive means capable of stimulating fullness sensations [74•]; the absence of caloric input associated with this approach allows for more naturalistic experiments separating the mechanosensory impact of gut distension from the caloric contents of a meal. Ingestible capsules for passive sensing of gut pressure, pH and temperature [75], and high-density electrogastrogram (EGG) arrays [76 •] have been developed, which could facilitate laboratory as well as ambulatory (i.e., real-world) assessments of gut physiology in eating disorders across different stages of illness recovery. The discovery of a cortical "gastric network" in the brain using simultaneous analysis of resting EGG and brain fMRI recordings [77•] lays the groundwork for experimental studies testing the state-specific role of this network as a homeostatic regulator of food intake and of motivationally relevant hunger and satiety cues [78].…”
Section: Methodological Challenges and Solutions To Studying Gastrointestinal Interoceptionmentioning
confidence: 99%
“… Mimee et al, 2018 ) and clinical research for non-invasive diagnostics of diseases affecting the GI system ( Mandsberg et al, 2020 ; Min et al, 2020 ; Rao et al, 2011 ), for local drug delivery ( Mandsberg et al, 2020 ), and for mapping heart rate, respiratory rate and apneic events, from within the human gastrointestinal tract ( Traverso et al, 2023 ). Interestingly, recent findings show that ingestible pills can be used to explore higher-order cognitive and emotional processes ( Mayeli et al, 2023 ; Mayeli et al, 2021 ; Monti et al, 2022 ). In particular, we used an ingestible capsule (SmartPill Motility Testing System, Medtronic plc) able to record pH, pressure and inner temperature throughout the entire GI tract ( Saad, 2016 ) when participants experienced the illusion of embodying a virtual breathing agent (referred to as the Embreathment, as described in Monti et al, 2020 ; Cantoni et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%